Unveiling New Horizons: AI-Driven Decision Support Systems in HRM - A Novel Bibliometric Perspective - Shantilawati, Irma; Suri, Oryza Intan; Sunarjo, Richard Andre; Anjani, Sheila Aulia; Robert, Dariari (Aptisi Transactions On Technopreneurship (ATT), 2025)
The integration of Artificial Intelligence (AI)-driven Decision Support Systems (DSS) in Human Resources Management (HRM) has become crucial for optimizing workforce management and enhancing decision-making processes. This bibliometric analysis investigates the research landscape of AI-driven DSS in HRM from 2015 to 2024, using data from the Dimensions database and analyzed through VOSviewer. Key trends, influential authors, and significant publications are identified, revealing the dominant roles of the United States, China, and India, with institutions like MIT, Stanford University, and IIT Delhi leading in productivity and impact. Notable contributors such as Dwivedi, Lowry, and Bose are highlighted for their practical and theoretical advancements in the field. Influential journals including "Decision Support Systems", "Information & Management", and "Sustainability" are identified as shaping the research landscape. The findings emphasize the transformative impact of AI-driven DSS on HRM practices, offering insights into future research opportunities and applications. This study provides a comprehensive framework for understanding the current state and future directions of AI-driven DSS in HRM, contributing to both academic and practical advancements.